Use case or activity diagram, that is the question! - Tatibana, Guilherme M. R.; Benitti, Fabiane Barreto Vavassori (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
This paper aims to analyze and measure the effects caused in the software development process by approaching two different ways to present the specification of requirements to a team that follows agile practices and compare with the approach already used. The two approaches selected were to include the use case artifacts and activity diagram to the specification and perform measurement guided by the GQM approach. Finally, with the results obtained in the case study, the recommendation that was established for the team that participated is the use of the activity diagram artifact to specify user stories high value estimating.